Kierkegaard e Guimarães Rosa: ressonâncias - Samczuk, Ingrid Bianchini (2010)
This research had as objective to analyze resonances of Kierkegaard s philosophy on the literature of João Guimarães Rosa, which has not as yet been done in this author s set of critics. The plausibility of this confrontation between these two authors is guided by Rosas s records, in letters and interviews, about his personal interest in Kierkegaard, also demonstrated by the finding of the philosopher s works and a book on Danish language in his personal library. Besides, there are two fulcrum points to this approximation: the concern about the individual and the importance of religion over their lives and the making of their works. From this starting point, we chose to analyze five narratives of the book Primeiras estórias, which are: As margens da alegria, Os cimos, A menina de lá, A terceira margem do rio and O espelho. In these stories, the protagonists were studied in order to demonstrate in which mesure each of them would represent the stages of existence theorized by the Danish thinker: aesthetic, ethical and religious. After the analysis, the Boy in As margens da alegria and Os cimos, together with Nhinhinha in A menina de lá were identified with the kierkegaardian s aesthete. To the ethics stage belongs the narrator of A terceira margem do rio, and to the religious stage we found the father in A terceira margem do rio, as well as O espelho s narrator. About this last character, it is worth saying that, among the ones listed to this study, it is the only one that travels through the three stages, in order to complete its movement of existential subjectification